Body Image, Rasio Lingkar Pinggang Panggul, dan Siklus Menstruasi pada Remaja Putri di SMK X Sidoarjo: Citra Tubuh dan Rasio Lingkar Pinggang Panggul Berhubungan dengan Siklus Menstruasi pada Remaja Putri di SMK X Sidoarjo - Farah Nuriannisa; Nanda Rizma Faradiba (Universitas Airlangga, 2023)
Background: In adolescent girls, sexual development is indicated by menarche. The irregular menstrual cycle is a sign of reproductive organ dysfunction. Negative body image and nutritional status are factors that can cause the menstrual cycle to be disrupted due to interference in estrogen hormone production. One of the nutrition status indicators that can be used is waist-hip ratio. Objectives: To analyzed the association between body image and waist-hip ratio with the menstrual cycle in adolescent girls at X High School Sidoarjo. Methods: This study was conducted with a cross-sectional design. The respondents enrolled in this study were 66 female students in X High School Sidoarjo. Body image data was collected using the Multidimensional Body Self Relation Appearance Scales (MBSRQ-AS) questionnaire, waist-hip ratio (RLPP) was measured with midline, and menstrual cycle was collected with menstrual cycle questionnaire. Data analysis used the Rank-Spearman correlation test. Results: The analysis showed that the average body image score was 80.4, the waist-hip ratio was 0,75, and the menstrual cycle was 34 days. The analysis also explained a significant association between body image and menstrual cycle (p-value=0.033, r-value=-0.262) and a significant correlation between waist-hip ratio and menstrual cycle (p-value=0.000, r-value=-0.504). Conclusions: There was a significant correlation between body image and waist-hip ratio with the menstrual cycle in adolescent girls at X High School Sidoarjo.